P2X7 receptor antagonism reduces the severity of spontaneous seizures in a chronic model of temporal lobe epilepsy. (June 2016) - Amhaoul, Halima; Ali, Idrish; Mola, Marco; Van Eetveldt, Annemie; Szewczyk, Krystyna; Missault, Stephan; Bielen, Kenny; Kumar-Singh, Samir; Rech, Jason; Lord, Brian; Ceusters, Marc; Bhattacharya, Anindya; et al.
Abstract: Background: The available pharmacotherapy for patients with epilepsy primarily address the symptoms and are ineffective in about 40% of patients. Brain inflammation gained support as potential target for developing new therapies, especially the P2X7 receptor (P2X7R), involved in processing of IL-1β, might be an interesting candidate. This study was designed to investigate the effect of a novel P2X7R antagonist on the severity and on the number of chronic spontaneous recurrent seizures (SRS), which was unexplored until now. Methods: After one-week of vehicle treatment (20% HP-β-cyclodextrin), JNJ-42253432 was administered subcutaneously for another week under continuous video-electroencephalography monitoring (n = 17) in Sprague Dawley rats 3 months after kainic acid-induced status epilepticus . The proportion of different seizure classes, as well as the number of SRS/day were calculated for the vehicle and treatment period. In addition, post-mortem microglial activation and astrogliosis were assessed. Results: A significant decrease of the proportion of type 4–5 SRS (p < 0.05), while an increase of type 1–3 was demonstrated (p < 0.05) from the vehicle to the treatment period. There was no effect of the P2X7R antagonist on the number of SRS/day or the glial markers. Conclusions: The P2X7R antagonist gave rise to a less severe profile of the chronic seizure burden without suppressing the SRS frequency. More studies are needed to unravel the underlying mechanisms of the beneficial effect on seizure severity and whether the administration of the compound during early epileptogenesis could induce long-term disease-modifying effects. Highlights: P2X7 receptor antagonism caused a shift in the severity of chronic seizures. A decrease in severe seizures was visible after one week of treatment. P2X7 receptor antagonism was unsuccessful in decreasing the number of seizures. P2X7 receptor antagonism did not alter microglial activation or astrogliosis.